Long-term anticoagulation treatment for acute venous thromboembolism in patients with and without cancer - Spirk, David; Ugi, Jörg; Korte, Wolfgang; Husmann, Marc; Hayoz, Daniel; Baldi, Thomas; Frauchiger, Beat; Banyai, Martin; Aujesky, Drahomir; Baumgartner, Iris; Kucher, Nils (Thrombosis and Haemostasis, 2011)
In patients with acute cancer-associated thrombosis, current consensus guidelines recommend anticoagulation therapy for an indefinite duration or until the cancer is resolved. Among 1,247 patients with acute venous thromboembolism (VTE) enrolled in the prospective Swiss Venous Thromboembolism Registry (SWIVTER) II from 18 hospitals, 315 (25%) had cancer of whom 179 (57%) had metastatic disease, 159 (50%) ongoing or recent chemotherapy, 83 (26%) prior cancer surgery, and 63 (20%) recurrent VTE. Long-term anticoagulation treatment for >12 months was more often planned in patients with versus without cancer (47% vs. 19%; p<0.001), with recurrent cancer-associated versus first cancer-associated VTE (70% vs. 41%; p<0.001), and with metastatic versus non-metastatic cancer (59% vs. 31%; p<0.001). In patients with cancer, recurrent VTE (OR 3.46; 95%CI 1.83–6.53), metastatic disease (OR 3.04; 95%CI 1.86–4.97), and the absence of an acute infection (OR 3.55; 95%CI 1.65–7.65) were independently associated with the intention to maintain anticoagulation for >12 months. In conclusion, long-term anticoagulation treatment for more than 12 months was planned in less than half of the cancer patients with acute VTE. The low rates of long-term anticoagulation in cancer patients with a first episode of VTE and in patients with non-metastatic cancer require particular attention.
Keywords: Anticoagulation; cancer; venous thromboembolism